Autism Spectrum Disorder Profile, Heterogeneity, Neurobiology and Intervention - Fitzgerald, Michael (IntechOpen, 2021)
Autism spectrum disorder (ASD) is a complex condition that has extreme heterogeneity, which makes it extremely challenging from a diagnostic and etiological point of view. To add to the complexity, ASD typically has co-morbidity and overlap with other conditions outlined in this book, including epilepsy, attention-deficit/hyperactivity disorder (ADHD), and others. This book also examines monocyte cytokine profiles and catecholamines in ASD, genetic studies of autism, treatments, and controversial issues.